WebTV / Leong Soon Hing - Leong , Soon Hing (2001)
This graduation project report was a partial requirement of the Bachelor Degree of Information Technology. This project focused on the testing and implementation of streaming multimedia files using multicast and unicast technology through Local Area Network with conserving network resources. It is also an effort being carried out to provide a multimedia and interactive base entertainment system for Faculty of Computer Science and Information Technology. Multimedia has become a popular catchword during the last few years. The idea behind a multimedia network is a single network combining an improving all current technologies that realizes fast and convenient access for the customer to voice. Data and video applications. The WebTV concept is first conceived to solve the weaknesses or traditional television in this demanding social. The WebTV is designed to he a multimedia environment, utilizing state-of-the-art currently powerful technology to accommodate user requirement. Since the study of multimedia broadcasting is still a new topic in computer world, only limited streaming technology available for this project. The core technology deployed in this project is Microsoft Windows Media Services 4. 1. which is a powerful streaming technology use for stream all on-demand and live broadcasting TV programs to users. Finally, it conclude that WebTV can be implemented using either unicast or multicast stream and all streams will he able to provide the optimum quality if implemented in Local Area Network.